2021
DOI: 10.3390/biology10080707
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Interactions between Brain States and Alzheimer’s Disease Pathology: A Focus on Gamma and Slow Oscillations

Abstract: Brain state varies from moment to moment. While brain state can be defined by ongoing neuronal population activity, such as neuronal oscillations, this is tightly coupled with certain behavioural or vigilant states. In recent decades, abnormalities in brain state have been recognised as biomarkers of various brain diseases and disorders. Intriguingly, accumulating evidence also demonstrates mutual interactions between brain states and disease pathologies: while abnormalities in brain state arise during disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 277 publications
0
12
0
Order By: Relevance
“…3,4 Along the same lines, recent findings showed the key role of gamma activity in ruling synaptic plasticity. [5][6][7][8] In animal models of AD, for instance, gamma oscillations decrease before the onset of plaque formation and the occurrence of cognitive decline, whereas the induction of fast-spiking activity at 40Hz reduces the level of amyloid-beta (Aβ) isoforms. 3 In addition, soluble Aβ oligomers have consistently been found to block long-term hippocampal potentiation (LTP), an electrophysiological correlate of learning and memory, in vivo and in vitro.…”
mentioning
confidence: 99%
“…3,4 Along the same lines, recent findings showed the key role of gamma activity in ruling synaptic plasticity. [5][6][7][8] In animal models of AD, for instance, gamma oscillations decrease before the onset of plaque formation and the occurrence of cognitive decline, whereas the induction of fast-spiking activity at 40Hz reduces the level of amyloid-beta (Aβ) isoforms. 3 In addition, soluble Aβ oligomers have consistently been found to block long-term hippocampal potentiation (LTP), an electrophysiological correlate of learning and memory, in vivo and in vitro.…”
mentioning
confidence: 99%
“…Another study, using a different DS model, also reported significant alterations of γ-oscillations and hypothesized that these changes could play a role in the pathophysiology of well-documented sleep disruptions in DS children [ 37 ]. It is also interesting, in the context of longer-term neuropathological alterations associated with DS (see below) that γ oscillations are known to be impaired in Alzheimer's disease (AD): this impairment correlates with the increased amyloid load in the CNS [ 38 ]. In fact, pharmacological restoration of γ oscillations is now considered a potential therapeutic approach to counteract various neurodegenerative processes [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of studies have reported elevated gamma activity in AD patients ( van Deursen et al, 2008 ; Başar et al, 2017 ). Although this contradictory observations may stem from various experimental parameters ( Byron et al, 2021 ), a recent study demonstrated that changes in gamma brain activity might be dependent on the degree of amyloid burden ( Gaubert et al, 2019 ). Hence, it is important for future studies to correlate AD pathology with changes in gamma oscillations ( Byron et al, 2021 ) as well as to clarify the role that the degree of pathogenesis plays in gamma brain activity.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%